2019
DOI: 10.1161/strokeaha.118.024449
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Risk of Major Ischemic and Hemorrhagic Events After Intracerebral Hemorrhage

Abstract: Background and Purpose— We aimed to determine incidences and predictors of major vascular events in intracerebral hemorrhage (ICH) survivors. Methods— We did a prospective observational cohort study in patients with spontaneous ICH from the Prognosis of Intracerebral Hemorrhage cohort in Lille, France. We studied incidences and predictors of long-term vascular events (cerebral and extracerebral, ischemic and hemorrhagic) in patients alive at 30 days wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 26 publications
4
97
1
3
Order By: Relevance
“…31 Our finding that in the youngest age-group, the risk of ICH appeared higher than the risk of ischaemic stroke may be explained by a larger proportion of underlying macrovascular causes (e.g., arteriovenous malformation, aneurysm, cavernoma) 33 and a lower prevalence of hypertension in this age-group compared to those of 55 years and older. 34 For ischaemic stroke, the one-year rate varied among previous studies between 0% and 7.0% (Supplementary Table e-5), 10,13,[16][17][18][19][20][21]24,27,28 with again the highest rate in the Scottish population. 27 The oneyear risk of a composite vascular outcome was assessed in six previous studies in ICH survivors and varied between 1 and 25%/year, 10,13,21,27,28,35 whereas in our study this risk was 4.3% in the youngest age-group and up to 14.6% in the elderly.…”
Section: Discussionmentioning
confidence: 92%
“…31 Our finding that in the youngest age-group, the risk of ICH appeared higher than the risk of ischaemic stroke may be explained by a larger proportion of underlying macrovascular causes (e.g., arteriovenous malformation, aneurysm, cavernoma) 33 and a lower prevalence of hypertension in this age-group compared to those of 55 years and older. 34 For ischaemic stroke, the one-year rate varied among previous studies between 0% and 7.0% (Supplementary Table e-5), 10,13,[16][17][18][19][20][21]24,27,28 with again the highest rate in the Scottish population. 27 The oneyear risk of a composite vascular outcome was assessed in six previous studies in ICH survivors and varied between 1 and 25%/year, 10,13,21,27,28,35 whereas in our study this risk was 4.3% in the youngest age-group and up to 14.6% in the elderly.…”
Section: Discussionmentioning
confidence: 92%
“…Optimising healthcare after ICH will therefore depend on the prognosis of ICH during long-term follow-up. However, currently available estimates come predominantly from hospital-based studies performed in the 1990s with relatively short follow-up, and focused mainly on recurrent stroke risk 2 3…”
Section: Introductionmentioning
confidence: 99%
“…Given the different balance of pathologies for lobar versus non-lobar ICH, the long-term prognosis of ICH could be expected to differ by haematoma location. However, while some studies suggested that haematoma location was associated with recurrent stroke,3–6 others have not 7 8. The impact of haematoma location on disability, dementia or quality of life in survivors up to 10 years after the initial ICH is also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…5 The annual risk of ICH recurrence is estimated to be 1.8-7.4%, 6 but in the long term, these patients are at even higher risk of ischaemic events like myocardial infarction and ischaemic stroke. 7,8 A substantial proportion of patients presenting with ICH are on antithrombotic treatment: a quarter use anticoagulant drugs, 9,10 and more than one-third use antiplatelet drugs. 11,12 Overall, 40-50% use, or have an indication for, antithrombotic treatment.…”
Section: Background and Aimsmentioning
confidence: 99%